KEUNEUNONG DAN ADAPTASI PETANI PADI DI GAMPONG UJONG DRIEN KABUPATEN ACEH BARAT - Azahra, Rahfa; Humaira, Humaira; Jumaini, Jumaini; Juliana, Juliana; Wannira, Ayu; Sopar, Sopar (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
Ujong Drien village, located in the Meureubo District, Aceh Barat Regency, is one of the farming communities that still maintains the local wisdom system in farming practices. Keuneunong, as a traditional calendar system of the Acehnese people, has been a generational guide for farmers in determining the ideal time for agricultural activities, particularly rice planting. This research aims to analyze the implementation of the keuneunong system as local wisdom in the adaptation of rice farmers in Ujong Drien village to face the challenges of climate change and agricultural modernization. This study uses a qualitative approach to understand the keuneunong practices and farmers' adaptation strategies. Data is collected through in-depth interviews with senior farmers, field observations of farming practices, and documentation of traditional knowledge still being practiced. The keuneunong system in Ujong Drien village shows unique characteristics as a nature observation-based calendar that includes 12 keuneunong (periods). Each keunenuong has specific indicators in the form of natural signs, animal behavior, and weather patterns that serve as guidelines for farmers in determining agricultural activities. Farmers' adaptation to climate change is carried out by integrating traditional keuneunong knowledge with modern weather information, adjusting rice varieties that are resilient to environmental stress, and modifying planting patterns according to changing climate conditions. ABSTRAKDesa Ujong Drien yang terletak di Kecamatan Meureubo, Kabupaten Aceh Barat, merupakan salah satu komunitas pertanian yang masih mempertahankan sistem kearifan lokal dalam praktik bercocok tanam. Keuneunong sebagai sistem penanggalan tradisional masyarakat Aceh, telah menjadi panduan turun-temurun bagi petani dalam menentukan waktu ideal untuk kegiatan pertanian, khususnya penanaman padi. Penelitian ini bertujuan untuk menganalisis implementasi sistem keuneunong sebagai kearifan lokal dalam adaptasi petani padi di Desa Ujong Drien menghadapi tantangan perubahan iklim dan modernisasi pertanian. Penelitian ini menggunakan pendekatan kualitatif  untuk memahami praktik keuneunong dan strategi adaptasi petani. Data dikumpulkan melalui wawancara mendalam dengan petani senior, observasi lapangan terhadap praktik pertanian, dan dokumentasi pengetahuan tradisional yang masih dipraktikkan. Sistem keuneunong di Desa Ujong Drien menunjukkan karakteristik unik sebagai kalender berbasis pengamatan alam yang meliputi 12 keunong (periode). Setiap keuneunong memiliki indikator spesifik berupa tanda-tanda alam, perilaku binatang, dan pola cuaca yang menjadi pedoman petani dalam menentukan aktivitas pertanian. Adaptasi petani terhadap perubahan iklim dilakukan dengan mengintegrasikan pengetahuan keuneunong tradisional dengan informasi cuaca modern, penyesuaian varietas padi yang tahan terhadap cekaman lingkungan, dan modifikasi pola tanam sesuai dengan kondisi iklim yang berubah.